Polyalkylimide: A Nonstable Filler Over Time. Issue 4 (April 2018) - Schelke, Leonie W.; Velthuis, Peter J.; van Dijk, Marijke R.
Abstract : BACKGROUND: Polyalkylimide hydrogel is supposed to be a permanent, biocompatible implant. However, years after subcutaneous implantation clinical complications are seen. OBJECTIVE: To increase the understanding of the changes that occur over time in this subdermal implanted filler. MATERIALS AND METHODS: The extruded filler material of 34 patients was evaluated by histologic examination. RESULTS: In most patients who had cosmetic disturbances but no complaints, histology showed no immune cells in or around the filler material. In patients with an acute inflammatory response, giant cell invasion was seen in and around the filler material. Patients with chronic complaints showed a neutrophilic cell influx in the extruded filler. In all patients, degeneration and calcification of the material was noted. The polyalkylimide hydrogel changed over time, both macroscopically and microscopically. As in most of the patients no immune response was seen around the filler material, this may indicate that the material is biocompatible. CONCLUSION: The authors conclude that a dermal filler should not be judged solely on its biocompatible characteristics but also on the degradation process over time in the human body.